University Engagements and Regional Specialisation – Comparative case study on regional engagements of universities in Finland and Sri Lanka and lessons learned - Sidath, Alwis (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Finland is considered among the first countries that adopted the national innovation system (NIS) framework as the foundation of their science and technology policy. Being a part of Finnish NIS framework, Finnish universities have been engaging with the regional development successfully. The policy makers and university authorities in Sri Lanka have growing interests on connecting the universities with the regional development process further. These backgrounds motivated to conduct a comparative study on the university engagements in regional development of two countries while focusing potential lessons learnt to Sri Lanka. The study mainly aims to understand the regional engagement of selected university institutions under the context of regional specialisations. With this purpose, the study attempts to identify the different engagement initiatives of selected cases located in different global locations and to understand how university can define its role in regional engagement concerning the regional specialisation. The analysis seeks to identify the potential lessons from each cases also. The research is an exploratory qualitative study, conducted based on case study methodology. The analysis was based on the data of thematic interviews and official publications. Thematic analysis method was used to assess the cases with reference to the regional needs and specialities and institutions potentials. The study identifies that the Finnish case does not comply with more industry oriented triple-helix model while locating in a well advanced industrial region. Finnish case attempts to address broader regional needs which are not focused by other institutions, such as further education in maritime sector. Therefore it depicts business–oriented engaged university model, playing a “developmental role” in regional engagement. It does not merely limit to engage in capital formation projects according to triple helix model. Sri Lankan case depicts community–oriented engaged university model, playing a “developmental role” in regional engagement focused to address broader regional needs of further education to agriculturists etc. It can be learned number of lessons from Finnish case. The research partnering with different stakeholders of maritime sector and strong stake holder links through regular contacts with them, have created successful and strong regional engagement opportunities to Finnish case. Similar attempts can be practiced by Sri Lankan case to unveil the opportunities to serve the needs of the stakeholders of commercial agriculture, consisted of input suppliers, machinery developers, growers, post-harvest processors etc.